Effectiveness and safety of ciprofol for the induction and maintenance of general anesthesia in urological surgery: a prospective, non-inferiority cohort study - Zhan, Ling; Xie, Shuang; Lu, Jing-xiao; Zhang, Fan (Frontiers in Medicine, 2025)
IntroductionCiprofol is a newly developed intravenous agent, with limited clinical data available to date. The study aimed to evaluate the effectiveness and safety of ciprofol for general anesthesia in patients undergoing urological surgery.MethodsThis study consecutively enrolled 172 urological patients aged ≥ 18 years who received general anesthesia. A total of 166 eligible patients were assigned to two groups: ciprofol (n = 85; induction 0.3–0.4 mg·kg−1; maintenance, 1.0–1.5 mg·kg−1·h−1) and propofol (n = 81; induction, 1.5–2.0 mg·kg−1; maintenance, 4–8 mg·kg−1·h−1). The primary effectiveness endpoint was the difference in anesthesia success rates between the two groups. The secondary effectiveness endpoints included the normal rate of the bispectral index (BIS), time to adequate sedation, time to loss of the eyelash reflex, diachronic changes in the BIS, mean arterial pressure (MAP), heart rate, recovery time, and extubation time. Adverse events (AEs) were recorded to evaluate the safety profiles of ciprofol.ResultsThe anesthesia success rate was 100% in both groups. The lower limit of the 95% confidence interval (CI) for the rate difference (RD) exceeded the prespecified non-inferiority margin of −10%. The time to adequate sedation and the time to loss of the eyelash reflex were longer with ciprofol compared to propofol (p < 0.001). The diachronic changes in the BIS and MAP in the ciprofol group decreased at a relatively slower rate during induction, indicating that ciprofol had a slower but smoother onset of action compared to propofol. The recovery time and extubation time were similar between the two groups. Ciprofol was associated with significantly lower incidences of injection pain, hypotension, and deep anesthesia compared to propofol. No patient in either group showed intraoperative awareness or postoperative cognitive decline.ConclusionCiprofol is non-inferior to propofol in terms of effectiveness and safety. It can be safely and effectively used for the induction and maintenance of general anesthesia in patients undergoing urological surgery.